Optimal Role of the Nephrologist in the Intensive Care Unit - Askenazi, D J; Heung, Michael; Connor, Jr, Michael J; Basu, Rajit K; Cerdá, Jorge; Doi, Kent; Koyner, Jay L; Bihorac, Azra; Golestaneh, Ladan; Vijayan, Anitha; Okusa, Mark D; Faubel, Sarah (Blood purification, 2017)
As advances in Critical Care Medicine continue, critically ill patients are surviving despite the severity of their illness. The incidence of acute kidney injury (AKI) has increased, and its impact on clinical outcomes as well as medical expenditures has been established. The role, indications and technological advancements of renal replacement therapy (RRT) have evolved, allowing more effective therapies with less complications. With these changes, Critical Care Nephrology has become an established specialty, and ongoing collaborations between critical care physicians and nephrologist have improved education of multi-disciplinary team members and patient care in the ICU. Multidisciplinary programs to support these changes have been stablished in some hospitals to maximize the delivery of care, while other programs have continue to struggle in their ability to acquire the necessary resources to maximize outcomes, educate their staff, and develop quality initiatives to evaluate and drive improvements. Clearly, the role of the nephrologist in the ICU has evolved, and varies widely among institutions. This special article will provide insights that will hopefully optimize the role of the nephrologist as the leader of the acute care nephrology program, as clinician for critically ill patients, and as teacher for all members of the health care team.